2003
DOI: 10.1007/s00467-002-1001-4
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and effect of aminoglycoside therapy during the first ten days of life

Abstract: The effect of aminoglycoside administration on kidney functional maturation was evaluated in groups of 30 preterm and 30 fullterm infants who were treated for 7 days because of suspected infection. One of three different aminoglycosides was administered to each subgroup of ten preterm and ten fullterm infants. Changes in tubular function in groups of ten preterm and ten fullterm infants who were not given antibiotics were also compared. The mean gestational age for preterm infants from 32.5 to 33.6 weeks and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
3
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 46 publications
4
39
3
7
Order By: Relevance
“…[9][10][11][12][13][14][15][16]48 Those meta-analyses showed no difference in clinical efficacy between ODD and MDD 9,13,14,16 or even better efficacy with ODD. [10][11][12]15 With the exception of severely ill children, clinical failures were uncommon in the trials we analyzed, regardless of the regimen used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16]48 Those meta-analyses showed no difference in clinical efficacy between ODD and MDD 9,13,14,16 or even better efficacy with ODD. [10][11][12]15 With the exception of severely ill children, clinical failures were uncommon in the trials we analyzed, regardless of the regimen used.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we observed a trend toward fewer bacteriologic failures, which again was consistent with the results of adult meta-analyses that evaluated this outcome. 10,11,14,15,48 One meta-analysis 9 of adult data suggested that ODD might reduce nephrotoxicity, whereas other meta-analyses [10][11][12][13][14][15]48 showed nonsignificant trends or no difference in nephrotoxicity outcomes. In our meta-analysis, we were not able to show any reduction in the risk of primary nephrotoxicity outcomes with ODD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in this regard, antibiotics such as the aminoglycosides can readily cross the placenta [98] and there have been a number of experimental studies linking antibiotics with impairment of nephrogenesis [99][100][101][102]. For instance, it has been shown that incubation of metanephroi in culture with gentamicin leads to decreased branching morphogenesis of the ureteric tree and thus reduced nephron formation [99].…”
Section: Antibioticsmentioning
confidence: 99%
“…It is known that antibiotics, such as the aminoglycosides, can be nephrotoxic in the newborn (with the preterm infant most vulnerable) [101] and they are also linked with impairment of nephrogenesis [103,173]. Administration of gentamicin in neonates has been shown to primarily result in renal tubular necrosis [100], which consequently leads to increased sodium excretion, proteinuria, and a significant reduction in GFR [101,181,182].…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation